2000
DOI: 10.1103/physrevb.61.15817
|View full text |Cite
|
Sign up to set email alerts
|

Ab initioprediction of the electronic and optical excitations in polythiophene: Isolated chains versus bulk polymer

Abstract: initio prediction of the electronic and optical excitations in polythiophene : isolated chains versus bulk polymer. Physical Review B, 61(23), 15817-15826. DOI: 10.1103/PhysRevB.61.15817 General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 41 publications
3
50
0
Order By: Relevance
“…32 A similar permittivity anisotropy can be found for crystalline polythiophene ͑PT͒. 33 In both PPV and PT, the permittivity principal component value ␤ zz is much larger than those in the other directions.…”
Section: -5supporting
confidence: 51%
“…32 A similar permittivity anisotropy can be found for crystalline polythiophene ͑PT͒. 33 In both PPV and PT, the permittivity principal component value ␤ zz is much larger than those in the other directions.…”
Section: -5supporting
confidence: 51%
“…15͒ and 0.6 eV, 16 respectively. We have demonstrated that by embedding a polythiophene chain in a medium with the appropriate frequency-dependent dielectric constants, the exciton binding energy is reduced to 0.76 eV, 13,14 while the optical gap remains virtually unaffected. A similar drastic reduction of the exciton binding energy by interchain screening effects was predicted earlier by Moore and Yaron 17 in polyacetylene, within the semiempirical Pariser-Parr-Pople theory.…”
Section: Introductionmentioning
confidence: 99%
“…Our numerical implementation has been outlined in our earlier publications. 13,14 We use the Car-Parrinello scheme 23 to obtain the DFT-LDA geometries of the single polymer chains and take the experimental crystal structures. 24,25 For PT this leads to an orthorhombic unit cell with aϭ14.80 ͑chain direction͒, bϭ14.75, and c ϭ10.45 a.u.…”
Section: Theory: the Quasiparticle And Bethe-salpeter Equationsmentioning
confidence: 99%
“…15͒ and 0.6 eV, 16 respectively. We have demonstrated that by embedding a polythiophene chain in a medium with the appropriate frequency-dependent dielectric constants, the exciton binding energy is reduced to 0.76 eV, 13,14 while the optical gap remains virtually unaffected. A similar drastic reduction of the exciton binding energy by interchain screening effects was predicted earlier by Moore and Yaron 17 in polyacetylene, within the semiempirical Pariser-Parr-Pople theory.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Green's function methods for the first-principles description of the electronic ͑one-particle͒ and optical ͑two-particle͒ excitations of extended systems have been developed and applied to several systems. [9][10][11] In the meantime, these methods have been applied to the conjugated polymers polyacetylene, 12 polyphenylenevinylene 12 ͑PPV͒, and polythiophene 13,14 ͑PT͒. For these three polymers calculations for an isolated polymer chain were performed, leading to a good agreement for the excitation energy of the lowest optically active singlet exciton, but a very large binding energy for this exciton.…”
Section: Introductionmentioning
confidence: 99%